The Integration of Religious Moderation Values in Islamic Education Learning for Strengthening Interfaith Tolerance at SMAN 1 Kuripan and SMKN 1 Kuripan, West Lombok - Sri Sukmawati; Parhaini Andriani (AS-SABIQUN, 2026)
Although religious moderation has become increasingly important in multicultural educational settings, comparative research on the integration of religious moderation values in Islamic Religious Education (PAI) learning remains limited. This study aims to analyze the forms of integration of religious moderation values in PAI learning at SMAN 1 Kuripan and SMKN 1 Kuripan, examine their impact on students’ interfaith tolerance, and assess their effectiveness in fostering inclusive school environments. This study employed a qualitative descriptive multi-site case study design involving two selected secondary schools. Data were collected through semi-structured interviews, non-participant observations, and documentation analysis, and were analyzed using interactive qualitative techniques consisting of data reduction, data display, and conclusion drawing supported by triangulation. The findings reveal that religious moderation values were integrated through three interconnected dimensions: classroom instructional practices, institutional policy support, and socio-cultural habituation within the school environment. At SMAN 1 Kuripan, integration was more evident through structured interfaith activities and institutional accommodation of religious diversity, whereas at SMKN 1 Kuripan, it was reflected in the normalization of equal participation and routine interpersonal interaction. The findings further indicate that moderation-based PAI learning strengthened students’ interfaith tolerance by fostering mutual respect, reducing prejudice, and supporting harmonious school relations. This study concludes that the integration of religious moderation values in Islamic education provides an effective framework for developing inclusive educational communities. The findings contribute to the discourse on knowledge integration in Islamic education and offer practical implications for educators and policymakers in strengthening moderation-based practices in pluralistic school contexts. Keywords: Inclusive School Environment; Interfaith Tolerance; Islamic Religious Education; Multicultural Education; Religious Moderation Values